School integration of mentall y deficient children: a historical study and some present-da y questions - C.Fourment-Aptekman, M.; Chapuis, E. (Clinical Styles. The Journal on the vicissitudes of childhood, 2000)
The authors, first of all, present a history of school integration of mental deficient children in France. Secondly, they discuss some contemporary problems on school integration. They conclude that the progress in this domain will be possible only if it is accompanied by a therapeutic situation based on transfer.